2012
DOI: 10.1007/s10231-012-0306-6
|View full text |Cite
|
Sign up to set email alerts
|

Plane algebraic curves with many cusps, with an appendix by Eugenii Shustin

Abstract: The maximum number of cusps on a plane algebraic curve of degree d is an open classical problem that dates back to the nineteenth century. A related open problem is the asymptotic value of the maximum number of cusps on plane curves of degree d, divided by d^2, when d tends to infinity. In this paper, we improve the best known lower bound for the asymptotic value by constructing curves with the largest known number of cusps for infinitely many degrees. Some particular curves of relatively low degree with many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It says that b ď" 125`?73 432 d 2 . In [6], there is constructed a family of curves with b " 2567 8640 d 2 (for some infinite sequence of d).…”
mentioning
confidence: 99%
“…It says that b ď" 125`?73 432 d 2 . In [6], there is constructed a family of curves with b " 2567 8640 d 2 (for some infinite sequence of d).…”
mentioning
confidence: 99%
“…The general genus formulas ( 6) and (7) were first proved by Hironaka [38,Theorem 2] using the resolution of the singularities of C (he defines g(C) as s i=1 g(C i )). If C ⊂ P 2 is a plane curve of degree d > 0, then C is connected (by Bezout's theorem) and we have (8) p…”
Section: This Is a Consequence Ofmentioning
confidence: 99%
“…Now, if C ⊂ P 2 is reduced and irreducible, then C is smooth and connected and the geometric genus g(C) = g(C) is non-negative. The formulas (6) and (8) imply the genus formula…”
Section: This Is a Consequence Ofmentioning
confidence: 99%
“…For cuspidal curves, a classical open problem is to determine the maximum number of cusps realizable on a plane curve of degree d; recent asymptotic results were proven by Calabri, Paccagnan, and Stagnaro [6]. Interestingly, Koras and Palka [19] showed that complex plane rational cuspidal curves possess at most four singular points.…”
Section: Introductionmentioning
confidence: 99%